2018
DOI: 10.1159/000487886
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Myasthenia Gravis in Slovakia in the Years 1977–2015

Abstract: Purpose: The objective of the study was to evaluate changes of epidemiological parameters in patients with myasthenia gravis (MG) in Slovakia during the period 1977–2015. Methods: Data from medical records of MG patients registered in Slovakia were analyzed. Epidemiological rates (incidence, prevalence, mortality) were assessed for several periods to identify changes and drifts over the period of study. Results: Out of 2,074 patients, 892 were males (43.0%) and 1,193 were females (57.0%). The thymoma associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
5
18
2
3
Order By: Relevance
“…Similar to the previous studies [9, 10, 12, 16, 19-23], we have observed an increasing incidence of symptomatic MG in LOMG. Carr et al [24] in a systematic review of population-based epidemiological studies in MG in the period 1950–2007 reported 3% increase of IR per year with significant increase after inputting AChRAb assays, with IR within 0.17–2.13/100,000.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the previous studies [9, 10, 12, 16, 19-23], we have observed an increasing incidence of symptomatic MG in LOMG. Carr et al [24] in a systematic review of population-based epidemiological studies in MG in the period 1950–2007 reported 3% increase of IR per year with significant increase after inputting AChRAb assays, with IR within 0.17–2.13/100,000.…”
Section: Discussionsupporting
confidence: 92%
“…Myasthenia gravis (MG) is a relatively rare disease, affecting about 140 people per million [1,2]; however, its frequency has been increasing in the recent years, especially in the elderly population with mortality rate of 0.27/100,000 people, and in intensive care units, mortality of such patients reaches 5.3% [3,4]. However, MG also affects children, manifesting in three forms: transient neonatal myasthenia, congenital myasthenic syndrome, and juvenile MG [5].…”
Section: Introductionmentioning
confidence: 99%
“…Two main observations emerge from these findings: The incidence of late‐onset AChR Ab‐positive MG significantly increased during the past decade and is responsible in large part for the overall increase in incidence in our study. This increased incidence of MG in the elderly has also been observed in other geographical areas during the past two decades 10,15‐20,23‐24,29,35‐38 The incidence ratio of AChR Ab‐positive MG between male and female patients (M:F) has also changed from the first to the second decade.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, the occurrence of MG is influenced by sex and age: Women are affected nearly three times more than men during early adulthood (<40 years), whereas incidence is roughly equal after this age 13,14 . Also, in the last decades, MG incidence in the elderly has increased, probably due to increased awareness and increased longevity 10,15‐24 …”
Section: Introductionmentioning
confidence: 99%